Effect of Loan Assets Classification on Financial Performance of Nigerian Listed Deposit Money Banks (British Journal of Multidisciplinary and Advanced Studies, 2023)
This ex post facto research study examines the effect of loan asset classifications and the impacts of substandard, doubtful, and loss loans on the financial performance of listed deposit money banks in Nigeria. The studied Population included all 14 deposit money banks listed on the Nigerian Stock Exchange (NSE) within the period of 2008 to 2019. The study purposively sampled 10 out of the 14 banks for the purpose of data collection and employed multiple regression analysis of data collated from the annual financial reports of the sampled banks within the studied period. In view of the absence of cross-section effect in the dataset, the pooled independent OLS regression was chosen for analysis and interpretation, revealing that the combined outcome of substandard (SSL) and loss loans (LL) variables are significantly related with the financial performance of listed deposit money banks in Nigeria, while doubtful loans show an insignificant effect on financial performance. The study concludes that bank loans are strong predictor of financial performance in Nigeria, thus it is recommended that banks should eradicate weaknesses such as underwriters’ initial failure to adequately assess borrower risk level prior to issuing loans and to subsequently successfully enforce repayment of the loans.